Strategies to Control and Prevent Novel Coronavirus 2019: A Quick Overview - Muhammad, Anees; Ali, Johar; Manan, Abdul; Khan, Hidayat; Owais, Muhammad (Journal of Liaquat University of Medical & Health Sciences, 2020)
The emergence of Novel Coronavirus (2019-nCoV) in the Wuhan City of China and its rapid shedding among countries, which reminded the history of Severe Acute Respiratory Syndrome (SARS) happened almost two decades ago. However, the genome sequence of 2019-nCoV shared within few days of outbreak shows the better response of China and the world against the virus, perhaps due to the availability of advanced technology and lesson learned from previous epidemics. The researchers trying to determine the virulence, pathogenicity and transmission of 2019-nCoV. It is believed that disease reporting and data sharing about the emerged Coronavirus with international researchers are important steps to reduce the spread of the virus to the rest of the world. This report is aimed to understand the current status of the 2019-nCoV, problems related to it and possible measures for prevention. The infection may spread through wildlife and asymptomatic patients. People in underdeveloped countries having no basic facilities are at higher risk. Ban on wildlife trade and avoiding unnecessary traveling for a certain period is required to minimize the spread of the disease. The use of face masks, keeping away from the public gathering are other possible means of precautions, capacity building of health workers and provided relevant facilities (equipment, kits, etc.) to underdeveloped countries will further help to contain the pandemic. In the current scenario, it is concluded that 2019-nCoV is spreading irrespective of the borders and become pandemic. Extensive research is a cry of the day to contain the virus and curtail human losses.